Pengembangan Media Pembelajaran Mandiri Berbasis Smartphone Pada Materi Kubus Tingkat MTs - Nadiya Yusuf; I Nyoman Arcana (UNION: Jurnal Ilmiah Pendidikan Matematika, 2018)
The present study aimed to (1) develop media-based learning of smartphone for learning mathematics in junior school, (2) to know the feasibility of media-based smartphone made. This research is a research and development (Research & Development), which is a research used to develop or validate the products used in learning. The development method used in this study follows a simple development procedure suggested by Borg & Gall consisting of five steps, namely (1) product analysis to be developed, (2) initial product development, (3) expert validation and product revision, 4) limited trial and product revision, (5) main trial and final product. The result of this study is media learning with the title " Smartphone Based Independent Learning Media for Junior High School Cube Material" which is packaged in a APK file in a Compact Disk (CD). The validation proved the feasible use of smartphone-based media learning. The feasibility is supported by the average media score of 86.5 (very good), the material score 93.5 (very good), the student response scores from 20 students in MTs N Ngablak with an average of 58.2 (very good). The validation of this feasibility is also supported by the average score of student learning result test equal to 85 with number of student reaching KKM 95% and existence of high correlation (r= 0,828) between score of student response test with score test result learning of students which means that there is an unidirectional relationship between students' questionnaire scores with test scores of student learning outcomes.